Computergeschützte Ermittlung morphometrischer Parameter aus topographischen Karten - Cyffka, Bernd (ERDKUNDE, 1989)
For a long time there have been several parameters frequently applied in hydrogeography als well as in geomorphology when comparing most differing research areas. Many calculations were necessary to work out these parameters. Now the EDP, based on the digital registration of the contents of a topographical map, offers the possibility to get more detailed results within a shorter period than before. In the following the program RELIEF, calculating the relief and form indices, river descent, length of the river, the river density as well as the drainage area and its volume, will be introduced. Thus this program supports morphometrical analysis of research areas. Moreover it enables longitudinal river profiles and channel networks of the research areas to be plotted by means of the computer.